Clustering of Expressed Sequence Tag (EST) with Markov Models and Self-Organizing Maps: An Exploratory Study - Ng, Keng Hoong; Somnuk, Phon Amnuaisuk; Ho, Chin Kuan (2008)
Expressed Sequence Tag (EST) plays an important role in discovering the full length of a gene. Therefore clustering of ESTs remains an interesting area for further exploration. We investigate several available clustering algorithms, and then we propose and evaluate an unsuperivsed clustering method that uses Markov models and Se self-organizing maps. The initial evaluation of the method gives satisfactory result, where its clustering accuracy is up to 80.08%.